A computational approach to the study of interactions between proteins and miR10-b, miR-335, and miR-21 involved in breast cancer - Rahma Hammou; Yassine Kasmi; Moulay Ennaji (Contemporary Oncology)
MiR-10b, miR-335, and miR-21 are classes of microRNAs (miRNAs) that are overexpressed in breast cancer. Thus, in our study we aimed to test the hypothesis that miRNAs may have direct interactions with proteins and the possibility to inhibit/activate the functional site of proteins and enzymes. For this purpose, we choose three miRNAs involved in breast cancer to study interactions between some proteins and genes, including BRCA1 and PTEN, by processing the docking and matching tools using the Hex8 and HADDOCK server. Mathematically, the hidden Markov models were created by using MATLAB script according to the algorithm in order to study and validate the interactions and bonds between proteins and miRNAs. The main results demonstrate the ability of miR-10b, miR-335, and miR-21 to create direct interactions with 3D protein structures. Furthermore, these results may lead to another pathway of research, i.e. the direct interaction between proteins and their sub-units, to highlight the data obtained previously and demonstrate that proteins may directly interact with ncRNA instead of mRNA. Moreover, our study suggests developing research on different pathways of association proteins-miRNAs as a part of epigenetic extra-nuclear regulation. Taken together, our study provides the first evidence of direct interactions between miRNAs and proteins.